Tasks of the National Police of Ukraine as a subject of implementation of the preventive function of the state - I. V. Ishchenko (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the tasks of the National Police of Ukraine as a subject of implementation of the preventive function of the state. It is emphasized that the tasks of the Department of Preventive Activities of the National Police of Ukraine are an important component of determining the specifics of its activities and administrative and legal status, as the effective implementation of the Department of Preventive Activities of the National Police of Ukraine depends on a clear legislative understanding of its tasks as body of state power.